2013
DOI: 10.2131/jts.38.803
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortex and hippocampus respond differently after post-natal exposure to uranium

Abstract: -The central nervous system (CNS) is known to be sensitive to pollutants during its development. Uranium (U) is a heavy metal that occurs naturally in the environment as a component of the earth's crust, and populations may therefore be chronically exposed to U through drinking water and food. Previous studies have shown that the CNS is a target of U in rats exposed in adulthood. We assessed the effects of U on behavior and cholinergic system of rats exposed from birth for 10 weeks at 10 mg.L -1 or 40 mg.L -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This behavioral toxicity is expressed by increased locomotor activity (Briner and Muray, 2005;Bellès et al, 2005), significantly decreased spatial working memory capacities , increased anxiety , and shorter paradoxical sleep . In addition to the cerebral cortex (Lestaevel et al, 2013), the hippocampus also seems to be a major target of U-induced neurotoxicity (Pellmar et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…This behavioral toxicity is expressed by increased locomotor activity (Briner and Muray, 2005;Bellès et al, 2005), significantly decreased spatial working memory capacities , increased anxiety , and shorter paradoxical sleep . In addition to the cerebral cortex (Lestaevel et al, 2013), the hippocampus also seems to be a major target of U-induced neurotoxicity (Pellmar et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…and metalloids. Such studies published these past three years in the Journal of Toxicological Sciences investigated the toxicity of many types of metals, including cadmium (Ohtani et al, 2013;Miura et al, 2013;Baba et al, 2014;Du et al, 2014;Park et al, 2015;Lukkhananan et al, 2015), mercury (Yoshida et al, 2013;Kim et al, 2014), methylmercury (Hwang et al, 2013a(Hwang et al, , 2013bIwai-Shimada et al, 2013;Chang et al, 2013;Hirooka et al, 2013;Kim et al, 2013;Watanabe et al, 2013;Shao et al, 2015;Toyama et al, 2015), aluminum (Zhang et al, 2013;Jinzhu et al, 2015), manganese (Fujishiro et al, 2013), uranium (Lestaevel et al, 2013), arsenic (Tokumoto et al, 2013;Wang et al, 2015), arsine (Kato et al, 2014), organic bismuth (Kohri et al, 2015), chromium (Kimura et al, 2015), and tributyltin (Oyanagi et al, 2015). Although methylmercury is one of the organic-inorganic hybrid molecules (the minimum unit!…”
mentioning
confidence: 99%
“…To support the latter hypothesis, Lestaevel and collaborators have previously demonstrated that U exposure from birth alters oxidative stress responses, metabolism of acetylcholine pathways as well as the metabolite profile in the cerebrospinal fluid in animals with impairment of neurobehavioral function [5,6,20]. …”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) is a target organ for many heavy metals and several reports have described neurological and neurobehavioral effects following internal exposure to U (for a review, see [4]), and more specifically during development. Briefly, U exposure from birth impairs object recognition and memory, causes anxiety and depressive-like behavior in adulthood and disturbs the balance of pro/antioxidant systems [5] and the cholinergic pathway [6]. Studies of animal models show that parental exposure to U during gestation and lactation impairs behaviors such as learning, activity, exploration, and emotionality in offspring [7,8,9].…”
Section: Introductionmentioning
confidence: 99%